An operant ethanol self-administration paradigm that discriminates between appetitive and consummatory behaviors reveals distinct behavioral phenotypes in commonly used rat strains. (15th December 2021) - Patwell, Ryan; Yang, Hyerim; Pandey, Subhash C.; Glover, Elizabeth J.
Abstract: Alcohol use disorder (AUD) constitutes a major burden to global health. Recently, the translational success of animal models of AUD has come under increased scrutiny. Efforts to refine models to gain a more precise understanding of the neurobiology of addiction are warranted. Appetitive responding for ethanol (seeking) and its consumption (taking) are governed by distinct neurobiological mechanisms. However, consumption is often inferred from appetitive responding in operant ethanol self-administration paradigms, preventing identification of distinct experimental effects on seeking and taking. In the present study, male Long-Evans, Wistar, and Sprague-Dawley rats were trained to lever press for ethanol using a lickometer-equipped system that precisely measures both appetitive and consummatory behavior. Three distinct operant phenotypes emerged during training: 1) Drinkers, who lever press and consume ethanol; 2) Responders, who lever press but consume little to no ethanol; and 3) Non-responders, who do not lever press. While the prevalence of each phenotype differed across strains, appetitive and consummatory behavior was similar across strains within each phenotype. Appetitive and consummatory behaviors were significantly correlated in Drinkers, but not Responders. Analysis of drinking microstructure showed that greater consumption in Drinkers relative to Responders is due to increased incentive for ethanol rather than increased palatability. Importantly, withdrawal from chronic ethanol exposure resulted in a significant increase in appetitive responding in both Drinkers and Responders, but only Drinkers exhibited a concomitant increase in ethanol consumption. Together, these data reveal important strain differences in appetitive and consummatory responding for ethanol and uncover the presence of distinct operant phenotypes. Highlights: A lickometer-equipped system revealed three distinct operant self-administration phenotypes. Drinkers exhibit appetitive and consummatory behaviors typical of operant self-administration. Responders fail to consume despite access to the reinforcer after appetitive responding. Both Drinkers and Responders escalate appetitive behavior during withdrawal. Direct measures of consumption are crucial for operant oral self-administration experiments.